2011
DOI: 10.1371/journal.pone.0027237
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Oxytocin Exposure Causes Persistent Reductions in Anxiety and Alcohol Consumption and Enhances Sociability in Rats

Abstract: Previous studies have suggested that administration of oxytocin (OT) can have modulatory effects on social and anxiety-like behavior in mammals that may endure beyond the time of acute OT administration. The current study examined whether repeated administration of OT to male Wistar rats (n = 48) during a key developmental epoch (early adolescence) altered their physiology and behavior in later-life. Group housed rats were given intraperitoneal injections of either 1 mg/kg OT or vehicle during early adolescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 92 publications
7
102
2
5
Order By: Relevance
“…It is through overstimulation and subsequent internalization of these receptors that rapid tolerance to ethanol's effects seems to develop (4). It is also possible that the effects described here are relevant to the inhibitory action of OT on ethanol consumption (12,19). A regionally specific knockdown of δ subunits in the medial shell of the nucleus accumbens reduces ethanol consumption in rats (6), whereas δ knockout mice are known to consume less ethanol than wild types (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is through overstimulation and subsequent internalization of these receptors that rapid tolerance to ethanol's effects seems to develop (4). It is also possible that the effects described here are relevant to the inhibitory action of OT on ethanol consumption (12,19). A regionally specific knockdown of δ subunits in the medial shell of the nucleus accumbens reduces ethanol consumption in rats (6), whereas δ knockout mice are known to consume less ethanol than wild types (5).…”
Section: Discussionmentioning
confidence: 99%
“…Early preclinical studies suggested that OT can prevent the development of tolerance to the sedative and ataxic effects of ethanol in rodents (10) and also modulate the severity of ethanol withdrawal (11). More recent studies show that OT reduces alcohol intake in rats (12) and reduces the severity of alcohol withdrawal and craving in dependent humans during detoxification (13). However, the mechanism underlying these actions is largely uncharacterized, including whether the modulation of various alcohol-related effects by OT involves the OT receptor (OTR).…”
mentioning
confidence: 99%
“…Finally, oxytocin systems play a role in various appetitive social behaviors, including pair bonding, mother-infant bonding, and social approach and recognition (Insel, 1992;Young et al, 2001;McGregor et al, 2008;Young et al, 2011). Male rats given oxytocin during early adolescence later exhibit enhanced social behavior, less anxiety-like behavior, and upregulated levels of oxytocin and oxytocin mRNA (Bowen et al, 2011). After oxytocin administration in adulthood, they also exhibit less alcohol drinking (Bowen et al, 2011), suggesting that upregulation of oxytocin may have a protective effect against alcohol intake (Bowen et al, 2011).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%
“…Male rats given oxytocin during early adolescence later exhibit enhanced social behavior, less anxiety-like behavior, and upregulated levels of oxytocin and oxytocin mRNA (Bowen et al, 2011). After oxytocin administration in adulthood, they also exhibit less alcohol drinking (Bowen et al, 2011), suggesting that upregulation of oxytocin may have a protective effect against alcohol intake (Bowen et al, 2011). Such systems are prime candidates for investigating the neural basis of social context at the time of drug initiation and on vulnerability to development of further drug use and dependence.…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%
“…Oxytocin reduces methamphetamine selfadministration, reinstatement of methamphetamine-seeking behavior, and methamphetamine-induced hyperactivity in rats [115]. Furthermore, oxytocin-treated rats show a reduction of anxiety-like behaviors and in alcohol consumption, and enhancement of social interaction as compared to controls [116]. Given these responses in laboratory animals, it is possible that oxytocin may be of value in treating similar symptoms in SRAD patients.…”
Section: Oxytocin and Addictive Behaviormentioning
confidence: 99%